The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1992
DOI: 10.1016/0022-1759(92)90276-y
|View full text |Cite
|
Sign up to set email alerts
|

A rapid isolation procedure for dendritic cells from mouse spleen by centrifugal elutriation

Abstract: The standard isolation procedure for antigen presenting dendritic cells (DC) takes 2 days and includes selective adherence to tissue culture plates which may lead to the activation of these cells. This report describes the isolation of DC by centrifugal elutriation (CE). Murine spleen cells were separated on the basis of size and density into 7 CE fractions. This method took 90 min. Ceils from each CE fraction were characterized by fluorescence activated cell sorter (FACS) analysis and their antigen presenting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
1
0

Year Published

1993
1993
2009
2009

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 40 publications
2
1
0
Order By: Relevance
“…These data agree with those obtained from LC, studied either in situ, shortly after isolation, or after short-term in vitro culture (15,(44)(45)(46). Similarly, culture of mouse DC leads to an increase in MHC class II expression and remodeling from a rounded morphology to one in which long cytoplasmic processes are present (47,48). Of note, MHC class II localization shifted from intracellular to the cell surface upon culturing.…”
Section: Discussionsupporting
confidence: 86%
“…These data agree with those obtained from LC, studied either in situ, shortly after isolation, or after short-term in vitro culture (15,(44)(45)(46). Similarly, culture of mouse DC leads to an increase in MHC class II expression and remodeling from a rounded morphology to one in which long cytoplasmic processes are present (47,48). Of note, MHC class II localization shifted from intracellular to the cell surface upon culturing.…”
Section: Discussionsupporting
confidence: 86%
“…Through subsequent immunomagnetic separation, using the same volume of selection reagents, DC could be purified in larger numbers compared with the apheresis product. Secondly, it was found that effector memory CD4 ' T cells were enriched and naive CD4 ' T cells depleted in Elutra F3 and F4, and this correlated with relatively The finding of DC enrichment in Elutra fractions is not necessarily unexpected as it has been described previously in two studies with non-clinical elutriation [12,14]. However, it has not been demonstrated previously using the Elutra system [10,15Á24], which differs from these nonclinical studies in several ways.…”
Section: Discussionsupporting
confidence: 62%
“…In addition, no surface antigens are specific for this population of cells (27). These problems were partially circumvented by the development of isolation procedures (28,31,34,39,41), which relied on the negative selection of DCs based on their lack of the cell surface antigens, such as CD2, CD3, CD14, CD16, CD19, CD20, CD56, and CD57, which are found on T lymphocytes, monocytes, neutrophils, B lymphocytes, and natural killer (NK) cells, respectively. Unfortunately, these procedures took 18-36 h and included several stages, one of which involved the selective adherence to tissue culture plates, which could lead to cell activation (14,16,32).…”
mentioning
confidence: 99%